Pharmacological and Safety Profile of Dexlansoprazole: A New Proton Pump Inhibitor – Implications for Treatment of Gastroesophageal Reflux Disease in the Asia Pacific Region - Goh, Khean Lee (J Neurogastroenterol Motil, 2016)
Although gastroesophageal reflux disease is not as common in Asia as in western countries, the prevalence has increased substantially during the past decade. Gastroesophageal reflux disease is associated with considerable reductions in subjective well-being and work productivity, as well as increased healthcare use. Proton pump inhibitors (PPIs) are currently the most effective treatment for gastroesophageal reflux disease. However, there are limitations associated with these drugs in terms of partial and non-response. Dexlansoprazole is the first PPI with a dual delayed release formulation designed to provide 2 separate releases of medication to extend the duration of effective plasma drug concentration. Dexlansoprazole has been shown to be effective for healing of erosive esophagitis, and to improve subjective well-being by controlling 24-hour symptoms. Dexlansoprazole has also been shown to achieve good plasma concentration regardless of administration with food, providing flexible dosing. Studies in healthy volunteers showed no clinically important effects on exposure to the active metabolite of clopidogrel or clopidogrel-induced platelet inhibition, with no dose adjustment of clopidogrel necessary when coprescribed. This review discusses the role of the new generation PPI, dexlansoprazole, in the treatment of gastroesophageal reflux disease in Asia.